Дослідження криптосистем на основі кодів хеш функцій - Жеков, І.; Караваєв, В. (ХНУРЕ, 2019)
This article is devoted to information security in post quantum epoch. The article discusses the security problems which could appear with quantum computer appearing and describes what have world's best minds do to prevent information's collapse.
Keywords: квантовий комп‘ютер; хеш-функція; алгоритм Шора; дискретний логарифм; NIST; криптоаналіз; криптосистема; стандартизація